The Extent of Awareness to Which the Academic Body and Students at the University of Nizwa Understand the Concept of Governance (Traditional and Electronic) - Attia, Huda Mohammed Juma; Al-Habsi, Radhia Sulaiman Nasser (Journal of Educational and Psychological Sciences, 2024)
The current study aims to investigate the extent of awareness among the academic body and students at the University of Nizwa regarding the concepts of traditional and electronic governance in the context of Oman. Qualitative methodology was employed to delve deeper into the study objectives and answer its inquiries comprehensively. Data was gathered through individual interviews with five faculty members and a group interview with four members of the Student Advisory Council. Through thematic analysis using MAXQDA software, the participants’ perspectives on the study’s theme were categorized into four main areas: The Conceptual and Visionary Framework, Principles of Electronic Governance, Stages of Electronic Governance Implementation, and Challenges in Electronic Governance Implementation. These categories further branched into several subcategories. The study provides recommendations based on the results, including the implementation of comprehensive awareness campaigns and targeted awareness programs. These initiatives aim to ensure that faculty members and students at the University of Nizwa gain a clear understanding of traditional and electronic governance concepts. Additionally, the study recommends incorporating governance-related subjects, encompassing both traditional and electronic aspects, into the academic curriculum, contributing to the formation of a more enlightened and proactive academic community. Furthermore, the researcher proposes conducting quantitative and qualitative studies with various designs, including a mixed-methods approach, such as the "blended design." This approach combines both quantitative and qualitative designs within the same study to generalize and apply the results to other universities.